2018
DOI: 10.1002/ldr.3005
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and transcriptional responses to salt stress in salt‐tolerant and salt‐sensitive soybean (Glycine max[L.] Merr.) seedlings

Abstract: Excess salinity is a major environmental threat to agriculture. However, the adaptive mechanisms underlying salt tolerance in soybean (Glycine max [L.] Merr.) remain unclear. The aim of this study was to investigate the differences between salt‐tolerant and salt‐sensitive soybeans in their physiological characteristics and the expression patterns of 8 cation antiporters under salt stress. The inhibitory effects of salt stress on growth and photosynthesis in salt‐sensitive soybean were stronger than those in sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 47 publications
(96 reference statements)
1
16
0
Order By: Relevance
“…These results suggest that the reason for photosynthesis under salt stress alone is nonstomatal limitation. Similar results were reported previously ( Feng et al, 2014 ; Ning et al, 2018 ) However, low pH with salt stress reduced the Ci and increased the Pn; Gs; and the activities of Rubisco, FBA and FBP. Taken together, these results indicated that low pH could protect photosynthetic structures and increase the photosynthesis enzyme activities, thereby increasing the photosynthesis rate.…”
Section: Discussionsupporting
confidence: 91%
“…These results suggest that the reason for photosynthesis under salt stress alone is nonstomatal limitation. Similar results were reported previously ( Feng et al, 2014 ; Ning et al, 2018 ) However, low pH with salt stress reduced the Ci and increased the Pn; Gs; and the activities of Rubisco, FBA and FBP. Taken together, these results indicated that low pH could protect photosynthetic structures and increase the photosynthesis enzyme activities, thereby increasing the photosynthesis rate.…”
Section: Discussionsupporting
confidence: 91%
“…The beneficial effect of CMB (extent of the decline in sodium accumulation) was significantly greater than with BR. Ning et al [ 34 ] demonstrated that soybean plants require more photosynthetic products in roots under saline stress to absorb sufficient moisture and nutrients to sustain regular growth. Under salt stress conditions, most of the energy acquired by photosynthesis and fixed into carbon compounds are used by plants for general maintenance, whereas only a small proportion (10–40%) is used directly for biomass accumulation [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…After harvesting and washing with deionized water, the root and leaf of soybean plants were separated. The sodium ion concentration measurement followed the procedure of [ 34 ]. Briefly, soybean leaves and roots were ground in an IKA mill (A11 basic, IKA) to a powder with uniform particle size.…”
Section: Methodsmentioning
confidence: 99%
“…Abdel Latef, Srivastava, El‐sadek, Kordrostami, and Lam‐Son Phan Tran () applied titanium dioxide nanoparticles to enhance tolerance of broad bean plants under saline soil, obtaining good effects and providing new ideas to improve salt‐affected soil in combination with bean planting. Ning, Kan, Shao, and Yu () investigated transcriptional responses to salt stress in salt‐tolerant and salt‐sensitive soybean ( Glycine max [L.] Merr.) seedlings and got two important salt‐tolerant genes (GmNHX1 and GmNcl1), providing potential base for biotechnologically breed soybean to meet salt‐resistant planting.…”
Section: Representative Advancesmentioning
confidence: 99%